Pregnancy while using a levonorgestrel-releasing intrauterine system 52 mg: a case report - Piriyev, Elvin; Romer, Thomas (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Intrauterine contraception mostly in the form of copper intrauterine device (IUD) or hormone-releasing system, is a widely used method with a high level of contraceptive security. Despite high contraceptive efficiency, pregnancy can still occur. Pregnancy with a levonorgestrel-releasing intrauterine system (LNG-IUS) in situ is very rare. Intracavitary pregnancy with an IUD can lead to a higher risk of infection and preterm birth. Present the case of a 28-year old woman who was admitted to our hospital due to pregnancy with an LNG-IUS 52 mg in the 9th gestational weeks (8 weeks 3 days). Sonography showed an intact pregnancy corresponding to the gestational week. The IUS was located in the lower part of the cavity at a considerable distance from the amniotic cavity. After extensive information on the benefits and risks, sonography-guided saline infusion hysteroscopy was carried out. The intact pregnancy and the IUS could be shown hysteroscopically. The removal of the IUS was carried out with a grasping forceps. There was no complication. After an inconspicuous course of pregnancy, the patient spontaneously gave birth in 37 gestational weeks 1 day.